Victory Communication Strategy Factors Influencing the General Election of the Governor of Riau - Hadrizal Hadrizal; Hamdan bin Mohd Salleh (Journal of Government and Political Issues, 2022)
This study examines the various forms of political communication strategies that influenced the victory of Syamsuar and Edy Nasution in the Riau Governor Election and evaluated the extent to which these strategies were effectively employed to win the competition. The research method used in this study is qualitative with a descriptive approach, where the findings are obtained through interviews and focus group discussions (FGD). The data collection technique used is qualitative, which will develop continuously (snowball method), and the data collection will stop when it reaches a saturation point. The study utilizes interviews and documentation as the primary data collection techniques. The findings reveal several factors that influenced voters, including mass media coverage, political party support, social proximity of individual candidates with voters, positive image of individual candidates, simple appearance that touched the hearts of voters, financial factors, and political marketing.